Zmiany w polityce państwa wobec mniejszości narodowych w 1952 roku na przykładzie Łemków osiedlonych na Ziemi Lubuskiej = The changes to the national minorities? policy in 1956, based on the example of the Lemkos settled in the Lubusz Land - Dudra, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main changes to the country?s policy regarding the national minorities, including the Lemkos population occurred in April 1952 and were connected with the resolution of the Politburo of the Polish United Workers Party. The resolution outlined the main issues concerning the ethnic matters that needed to be addressed.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia